Analisis Wacana Kritis (CDA) Lakon Mintaraga dalam Pagelaran Wayang Kulit - Aris Wahyudi; Farhan Khumaini; Krystiadi Krystiadi (Wayang Nusantara: Journal of Puppetry, 2022)
AbstractMintaraga play, so called Arjuna Wiwaha play, is an important performance in wayang tradition. Its significance is equal to Dewaruci or Sastrajendra play as it is considered as classical play containing Javanese spiritual teachings. Having been analysed using critical discourse analysis (CDA), this study reveals new values that represent the socio-political reality of the era. The values are rejections of social hegemony, particularly caste, which closely linked to the power system.AbstrakLakon Mintaraga yang sering disebut lakon Arjuna Wiwaha merupakan lakon penting dalam tradisi wayang. Keberadaannya sering disejajarkan dengan lakon Dewaruci atau lakon Sastrajendra yang dipandang sebagai lakon sepuh yang mengandung ajaran spiritual Jawa. Realitas di atas, setelah ditelaah dengan analisis wacana kritis (CDA), ternyata diperoleh nilai-nilai baru yang mempresentasikan realitas sosial politik yang mewakili nafas zamannya. Nilai-nilai tersebut adalah penolakan terhadap hegemoni sosial terutama tentang kasta yang berkaitan erat dengan sistem kekuasaan.